The role of multiparametric magnetic resonance in bladder cancer management - Katarzyna Kuźlik-Gołębiowska; Anna Jurkowska; Dariusz Gołębiowski; Katarzyna Sklinda; Jerzy Walecki; Wojciech Rogowski (Wiedza Medyczna, 2021)
Multiparametric magnetic resonance imaging with VI-RADS is a newly discussed method of diagnosing bladder cancer. There are more studies suggesting implementation of mpMRI with VI-RADS to the modern scheme of treating bladder cancer. It requires much more observation and trials to give a final recommendations. The aim of the summary is to present VI-RADS scale and possibilities that appear with the method. Many studies, that were made by departments of urology or radiology, showed promising results.Background: estimation of bladder cancer depends on proper tumor staging, grading and assessment of its biological potential. It is provided by a multimodal approach using clinical, histopathological and radiological methods. Development of MRI provides the best imaging technique for locoregional staging in several other tumors. Lately it was adjusted in BCa preoperative evaluation leading to significant improvement in differentiating patients with NMIBCs and MIBCs.Objective: this article aims to approximate the fundamentals of MRI in BCa and to provide an overview of the available data on the role of VI-RADS score in the diagnostic pathway of bladder cancer.